From periodontal mechanoreceptors to chewing motor control: A systematic review. (June 2017) - Piancino, Maria Grazia; Isola, Gaetano; Cannavale, Rosangela; Cutroneo, Giuseppina; Vermiglio, Giovanna; Bracco, Pietro; Anastasi, Giuseppe Pio
Highlights: This critical review summarizes the current knowledge of the structural and functional characteristics of periodontal mechanoreceptors. Histological and electrophysiological studies in animals: are the results in agreement? Molecular and electrophysiological studies in humans: what do we really know? Central connections of the trigeminal primary afferent neurons: is there a bias? From mechanotransduction to signal pathways: the role of periodontal mechanoreceptors on the chewing pattern motor control. Abstract: Purpose: This critical review summarizes the current knowledge of the structural and functional characteristics of periodontal mechanoreceptors, and understands their role in the signal pathways and functional motor control. Method: A systematic review of the literature was conducted. Original articles were searched through Pubmed, Cochrane Central database and Embase until january 2016. Result: 1466 articles were identified through database searching and screened by reviewing the abstracts. 160 full-text were assessed for eligibility, and after 109 exclusion, 51 articles were included in the review process. Studies selected by the review process were mainly divided in studies on animal and studies on humans. Morphological, histological, molecular and electrophysiological studies investigating the periodontal mechanoreceptors in animals and in humans were included, evaluated and described. Conclusion: Our knowledge of the periodontal mechanoreceptors, let us conclude that they are very refined neural receptors, deeply involved in the activation and coordination of the masticatory muscles during function. Strictly linked to the rigid structure of the teeth, they determine all the functional physiological and pathological processes of the stomatognathic system. The knowledge of their complex features is fundamental for all dental professionists. Further investigations are of utmost importance for guiding the technological advances in the respect of the neural control in the dental field.